Copper powder
By controlling the carbon content and oxygen content in copper powder, and using the C1s spectral characteristics with a high energy side peak area ratio greater than 0.5, low-temperature sintering of copper powder is achieved, solving the problem of insufficient sintering temperature of copper powder in the prior art, ensuring that The stability and properties of the conductive paste are achieved.
Patent Information
- Application Number
- CN202280096144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2022-07-29
- Publication Date
- 2025-01-03
Smart Images

Figure BDA0005136128360000091 
Figure HDA0005136128370000011
Abstract
Description
Technical Field
[0001] This specification discloses a technology related to copper powder. Background Art
[0002] Among the conductive pastes containing copper powder and used for forming a circuit on a substrate by printing, bonding a semiconductor element to a substrate, and the like, there is a sintering type conductive paste in which the copper powder contained in the paste is sintered by heating during use.
[0003] Sintering conductive paste requires copper powder to be sintered at a relatively low temperature. The reason is that when the temperature during heating is high, the heat may affect the substrate and semiconductor elements. In addition, when heating at high temperature and cooling after heating, large thermal stress is generated in the substrate or semiconductor elements, which may also change the electrical characteristics of the circuit and semiconductor elements.
[0004] It should be noted that in Patent Document 1, the technical problem is to provide a copper powder and a copper paste for a copper powder coating film that can be electrolessly plated with a metal without using an expensive catalyst such as palladium in the manufacture of a conductive coating film, and a method for efficiently forming a conductive coating film by electrolessly plating a copper powder coating film formed using the copper paste. The invention proposes a copper powder having an average particle size of 0.05 to 2 μm as observed by SEM, and a BET specific surface area value (SSA) (m 2 / g) and carbon content (C) (weight %) are in the relationship of the following formula [1]. C / SSA ≤ 7×10 -2 ……[1]”.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2012 / 157704 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Various studies and developments have been conducted on low-temperature sintering of copper powder, but sintering at even lower temperatures is sometimes required.
[0010] This specification discloses a copper powder having excellent low-temperature sinterability.
[0011] Solutions for solving problems
[0012] In the copper powder disclosed in this specification, the carbon content C (mass %) and the BET specific surface area (m 2 / g) ratio (C / SSA) is less than 0.07, and in the C1s spectrum obtained by X-ray photoelectron spectroscopy, the peak area ratio (A2 / A1) of the peak area A2 having a peak top in the range of 288eV to 289.2eV to the peak area A1 having a peak top in the range of 284eV to 285eV is greater than 0.5.
[0013] Effects of the Invention
[0014] The copper powder has excellent low-temperature sintering properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the C1s spectrum obtained by XPS in Inventive Example 5. DETAILED DESCRIPTION
[0016] Hereinafter, embodiments of the copper powder will be described in detail.
[0017] In the copper powder of one embodiment, the carbon content C (mass %) and the BET specific surface area (m 2 / g) ratio (C / SSA) is less than 0.07, and in the C1s spectrum obtained by X-ray photoelectron spectroscopy, the peak area ratio (A2 / A1) of the peak area A2 having a peak top in the range of 288eV to 289.2eV to the peak area A1 having a peak top in the range of 284eV to 285eV is greater than 0.5.
[0018] The details of such copper powder will be described later. The carbon content C (mass %) and the BET specific surface area (m 2 / g) ratio (C / SSA) is small, so it is easy to sinter at a relatively low temperature. In addition, in the above-mentioned copper powder, the specified peak area ratio (A2 / A1) in the C1s spectrum obtained by XPS is large. Here, the peak with a peak top in the range of 284eV to 285eV corresponds to the carbon bonded to the carbon atom, and the peak with a peak top in the range of 288eV to 289.2eV on the higher energy side corresponds to the carbon forming a double bond with oxygen. It can be considered that the copper powder with a large peak area ratio (A2 / A1) contains organic matter with a high oxygen content. If the organic matter with a high oxygen content is heated to more than several hundred degrees, it is easy to produce CO and CO2 due to thermal decomposition, and it is not easy to leave solid carbon in the form of thermal decomposition residue. Therefore, it can be considered that the copper powder coated with organic matter with a high oxygen content is easy to sinter at a relatively low temperature. However, it is not limited to such a theory.
[0019] (BET specific surface area)
[0020] The BET specific surface area of the copper powder is preferably 0.5 m 2 / g or more and 10.0m 2 / g or less. The BET specific surface area is greater than 10.0m 2 / g, it is difficult to ensure oxidation resistance, and the paste properties may have problems due to moisture absorption, agglomeration, etc. On the other hand, if the BET specific surface area is too small, the particle size of the copper powder is large and it may not sinter at low temperatures; the circuit printed with the paste and the smoothness of the joint surface are not sufficient. From this point of view, the BET specific surface area of the copper powder is preferably 0.5m 2 / g~10.0m 2 / g, and more preferably 2.0m 2 / g~6.0m 2 / g.
[0021] The BET specific surface area of the copper powder can be measured in accordance with JIS Z8830:2013, for example, by degassing the copper powder in a vacuum at 70° C. for 5 hours and then using BELSORP-mini II manufactured by MicrotracBEL.
[0022] (Average particle size)
[0023] The average particle size of the copper powder is preferably 0.05 μm to 2.00 μm, more preferably 0.05 μm to 1.50 μm, and particularly preferably 0.1 μm to 0.5 μm. If the average particle size of the copper powder is too large, it may not sinter at low temperatures, and the smoothness of the circuit and the bonding surface printed with the paste may be insufficient. In addition, if the average particle size of the copper powder is too small, it is difficult to ensure oxidation resistance, and the paste properties may have problems due to moisture absorption, agglomeration, etc.
[0024] The average particle size of the copper powder can be calculated using the following formula from the value of the BET specific surface area.
[0025] D = 6 / (ρ×SSA)
[0026] Here, D is the average particle size, ρ is the true density of copper, and SSA is the BET specific surface area.
[0027] (C / SSA)
[0028] Copper powder usually contains carbon because organic reducing agents and dispersants are used in its manufacturing process. 2When the carbon content (mass %) of the copper powder is set as "SSA" and the carbon content (mass %) of the copper powder is set as "C", with respect to the copper powder of the embodiment, their ratio (C / SSA) is 0.07 or less. When the ratio (C / SSA) is greater than 0.07, the carbon content is too much relative to the BET specific surface area, thereby obtaining excellent preservation and dispersibility, but in the sintering process, carbon remains on the surface of the copper powder in the form of thermal decomposition residues of organic reducing agents and dispersants, and it is not easy to sinter the copper powder. That is, the low-temperature sintering property is impaired. Therefore, the above ratio is 0.07 or less, and more preferably 0.05 or less.
[0029] On the other hand, if the carbon content C (mass %) and the BET specific surface area (m 2 If the ratio (C / SSA) of 100 g / g is too small, the oxidation resistance may be impaired or the compatibility with the organic solvent may be poor, resulting in a paste with poor dispersibility. Therefore, the ratio (C / SSA) is preferably 0.01 or more, and more preferably 0.02 or more.
[0030] Used to calculate carbon content C (mass %) and BET specific surface area (m 2 The carbon content of the copper powder with a ratio of 100 g / kg (C / SSA) is measured by high-frequency induction heating furnace combustion-infrared absorption method. Specifically, the carbon content of the copper powder can be measured using a carbon sulfur analyzer such as LECO CS844, with the combustion aid being set to LECO LECOCEL II and Fe sheet, etc., and a steel pin as the calibration curve.
[0031] (O / SSA)
[0032] In order to make the organic matter contained in the copper powder disappear in the form of CO and CO2 due to thermal decomposition during the sintering process, it is necessary to contain oxygen in the copper powder. 2 When the oxygen content (mass %) of the copper powder is set as "SSA" and the oxygen content (mass %) of the copper powder is set as "O", the ratio (O / SSA) of the copper powder of the embodiment is greater than 0.15. If the ratio (O / SSA) is greater than 0.15, the organic matter contained in the copper powder is easily converted into CO and CO2 during the sintering process, and the copper powder has excellent low-temperature sintering properties. The above ratio (O / SSA) is preferably a value greater than 0.15, and more preferably 0.17 or more.
[0033] Oxygen content O (mass %) and BET specific surface area (m 2 The ratio (O / SSA) of the copper powder to the organic matter (g) is preferably 0.5 or less, and more preferably 0.3 or less. This is because if the ratio (O / SSA) is too large, it means that oxygen not only comes from the oxidation of organic matter, but also the surface of the copper powder is significantly oxidized, which has the effect of destabilizing the properties of the paste prepared using the copper powder.
[0034] Calculate the oxygen content O (mass %) and BET specific surface area (m 2 The oxygen content of the copper powder used in the determination of the oxygen content of the ratio of carbon dioxide to nitrogen (O / SSA) was determined by inert gas fusion-infrared absorption. Here, TC600 manufactured by LECO was used as an oxygen and nitrogen analyzer, and a calibration curve was obtained by using a fiber optic. The copper powder was placed in a nickel bag for measurement.
[0035] (XPS peak area ratio)
[0036] When the copper powder is analyzed by X-ray photoelectron spectroscopy, a C1s spectrum, which is a spectrum of the 1s orbit of C, is obtained as the analysis result. In the C1s spectrum, the peak area ratio (A2 / A1), which is the ratio of the area A2 of the peak having a peak top in the range of 288 eV to 289.2 eV to the area A1 of the peak having a peak top in the range of 284 eV to 285 eV, is 0.5 or more.
[0037] Here, the peak of 284eV to 285eV corresponds to the electron of the 1s orbit of carbon that is not bonded to an atom with high polarity such as oxygen. Here, it is identified as corresponding to carbon with a C-C bond. On the other hand, the peak of 288eV to 289.2eV on the high energy side corresponds to the electron of the 1s orbit of carbon bonded to an atom with high polarity such as oxygen, and here, it is identified as corresponding to carbon with a C-O double bond. In the case where the copper powder contains an organic matter with a lot of oxygen, the peak intensity of the latter is relatively high compared to the peak intensity of the former, and the peak area ratio (A2 / A1) is large. When the peak area ratio (A2 / A1) is 0.5 or more, when the copper powder is heated, CO and CO2 are easily generated in the form of thermal decomposition products of organic matter, and carbon as a thermal decomposition residue is not easy to remain on the surface of the copper powder. Therefore, it can be considered that the sintering of the copper powder is easy to proceed at a relatively low temperature. From this point of view, the peak area ratio (A2 / A1) is more preferably 0.6 or more. On the other hand, the peak area ratio (A2 / A1) is usually not more than 10, and may be 1.0 or less.
[0038] In the C1s spectrum obtained by X-ray photoelectron spectroscopy, the peak area ratio (A3 / A1), which is the ratio of the area A3 of the peak having a peak top in the range of 286eV to 288eV to the area A1 of the peak having a peak top in the range of 284eV to 285eV, is preferably 0.3 or more.
[0039] It should be noted that the area of the peak having a peak top at the position of 288 eV is regarded as the area A2.
[0040] The peaks at 286 eV to 288 eV correspond to carbon atoms that form a single bond with oxygen. Copper powders having a peak area ratio (A3 / A1) of 0.3 or more have excellent low-temperature sintering properties, but the reason for this is unknown. The peak area ratio (A3 / A1) is preferably 0.3 to 0.7, and more preferably 0.3 to 0.5.
[0041] In order to obtain the peak area ratio (A2 / A1) and the peak area ratio (A3 / A1), X-ray photoelectron spectroscopy (XPS) measurement and analysis were performed as follows.
[0042] Apparatus: PHI 5000 Versa Probe II (with neutralizing gun) manufactured by ULVAC-PHI Corporation.
[0043] Excitation source: monochromatized AlKα.
[0044] Output:25.0W.
[0045] Detection area: 100μmΦ.
[0046] Angle of incidence: 90 degrees.
[0047] Take-off angle: 45 degrees.
[0048] In the measurement, the copper powder was formed into pellets for measurement.
[0049] The data analysis after the measurement was performed using data analysis software: MultiPak manufactured by ULVAC-PHI Co., Ltd. In the data analysis, the Voigt function was used to perform peak segmentation and calculate the area of each peak. In addition, the position of the peak with the lowest binding energy among the peaks attributable to C1s was corrected to 284.8 eV.
[0050] (Low temperature sintering)
[0051] In addition, the copper powder can be sintered at a relatively low temperature. The low-temperature sintering property can be confirmed as follows. About 0.3 g of copper powder is filled into a cylindrical mold with a diameter of 5 mm and uniaxially pressed to produce a cylindrical powder particle with a height of about 3 mm and a density of 4.7±0.1 g / cc. Afterwards, a thermomechanical analyzer (TMA) is used to heat the powder particles from 25°C at a rate of 10°C / min in an atmosphere containing 2 volume % hydrogen (H2) and the rest nitrogen (N2). At this time, as the temperature rises, the copper particles constituting the powder particles are sintered, and the volume of the powder particles decreases, approaching the density of metallic copper (about 8.9 g / cm 3 ). When the rate of change of the cylinder height in the shrinkage direction of such a compressed powder particle is called a linear shrinkage, the one with a lower temperature when the linear shrinkage is 5% can be evaluated as a copper powder having excellent low-temperature sintering properties. In particular, the temperature when the linear shrinkage is 5% is preferably 350°C or less.
[0052] (Manufacturing method)
[0053] The copper powder as described above can be produced, for example, by using a chemical reduction method or a disproportionation method, etc. The production of the copper powder is not limited thereto, and the details of the chemical reduction method are as follows.
[0054] When a chemical reduction method is used, for example, the following steps are performed in sequence: a step of preparing a copper salt aqueous solution, an alkaline aqueous solution, and a reducing agent aqueous solution as raw material solutions; a step of mixing and reacting these raw material solutions to obtain a slurry containing copper particles; a step of washing the copper particles; a step of performing solid-liquid separation; a step of drying; and a step of pulverizing as needed.
[0055] In a more specific example, after heating the copper sulfate aqueous solution to an appropriate reaction temperature, adjusting the pH with a sodium hydroxide aqueous solution and an ammonia aqueous solution, a hydrazine aqueous solution is added at once to react, and the copper sulfate is reduced to cuprous oxide particles with a particle size of about 100 nm. After heating the slurry containing the cuprous oxide particles to the reaction temperature, an aqueous solution containing sodium hydroxide and hydrazine is added dropwise, and then a hydrazine aqueous solution is added dropwise, thereby reducing the cuprous oxide particles to copper particles. After the reaction is completed, the obtained slurry is filtered, then washed with pure water and methanol, and then dried. Copper powder is thus obtained.
[0056] A reducing agent such as hydrazine added to the copper sulfate aqueous solution is used to reduce divalent copper to monovalent copper (cuprous oxide). At this time, if the reducing agent is added at once, the cuprous oxide particles thus generated tend to become fine as described above. After the finer cuprous oxide particles are generated, the reducing agent can be added separately. After the cuprous oxide particles are generated, the reducing agent added for the first time can be mainly used for the generation of the nucleus of metallic copper, and the reducing agent added for the second time can be used for the growth of the nucleus of the metallic copper.
[0057] It should be noted that, in the above-mentioned production, an aqueous solution of copper sulfate or copper nitrate can be used as the copper salt aqueous solution. The alkaline aqueous solution is sometimes specifically an aqueous solution of NaOH, KOH or NH4OH. As the reducing agent of the reducing agent aqueous solution, in addition to hydrazine, organic substances such as sodium borohydride and glucose can also be listed.
[0058] Alternatively, organic substances such as complexing agents and dispersants may be added during the process of manufacturing copper powder as needed. For example, gelatin, ammonia, gum arabic, etc. may be added once or more between the step of preparing the raw material solution and the step of obtaining the slurry containing copper particles.
[0059] (use)
[0060] The copper powder produced in this way is mixed with a resin material, a dispersion medium, etc. to form a paste, and is particularly suitable for use in a conductive paste that can be used for bonding a semiconductor element to a substrate and forming wiring.
[0061] Example
[0062] Next, the copper powder was produced by trial and its effect was confirmed, so the following description is given. However, the description here is for the purpose of illustrating an example only and is not intended to be limiting to this.
[0063] (Invention Example 1)
[0064] First, 6.7 L of a mixed aqueous solution of 540 g of sodium hydroxide and 144 g of hydrazine monohydrate was mixed at once into an aqueous solution obtained by dissolving 2400 g of copper sulfate pentahydrate and 30 g of citric acid in 8.7 L of pure water to synthesize a slurry containing nanoparticles of cuprous oxide (average particle size of about 100 nm). Next, the slurry in which the cuprous oxide particles were suspended was heated to above 50°C, 4.5 L of a mixed aqueous solution of 29 g of hydrazine monohydrate and 252 g of sodium hydroxide was added dropwise, and a sodium hydroxide aqueous solution was added to adjust the pH. After that, 1.3 L of an aqueous solution of 115 g of hydrazine monohydrate was further added dropwise to reduce the cuprous oxide to metallic copper. After the reaction was completed, decantation was repeated, and the mixture was washed with water, dried, and pulverized to obtain copper powder.
[0065] (Invention Example 2)
[0066] The process until the slurry containing cuprous oxide was synthesized was the same as that of Inventive Example 1. Next, 4.5 L of a mixed aqueous solution of 43 g of hydrazine monohydrate and 252 g of sodium hydroxide was added dropwise to adjust the pH, and 1.3 L of an aqueous solution of 101 g of hydrazine monohydrate was further added dropwise to reduce cuprous oxide to metallic copper, and the mixture was washed with water, dried, and pulverized in the same manner.
[0067] (Invention Examples 3, 4, and 5)
[0068] The process until the slurry containing cuprous oxide was synthesized was the same as that of Inventive Example 1. Next, 4.5 L of a mixed aqueous solution of 72 g of hydrazine monohydrate and 252 g of sodium hydroxide was added dropwise to adjust the pH, and 1.3 L of an aqueous solution of 72 g of hydrazine monohydrate was further added dropwise to reduce cuprous oxide to metallic copper, and the mixture was washed with water, dried, and pulverized in the same manner.
[0069] (Comparative Example 1)
[0070] To an aqueous solution obtained by dissolving 2400g of copper sulfate pentahydrate and 30g of citric acid in 8.7L of pure water, 6.7L of a mixed aqueous solution of 540g of sodium hydroxide and 144g of hydrazine monohydrate was added dropwise to synthesize cuprous oxide. Next, the slurry in which cuprous oxide was suspended was adjusted to 70°C, and an aqueous sodium hydroxide solution was added to adjust the pH value to 10. After that, 14g of hydrazine monohydrate and sodium hydroxide were added to start reducing part of the cuprous oxide to metallic copper. After further adding an aqueous solution of citric acid, hydrazine monohydrate was added, and the reduction was carried out steadily for several hours. After the reaction was completed, it was washed with water, dried, and crushed to obtain a copper powder. 2L of an aqueous solution containing 0.3g of malonic acid with a high oxygen concentration and a small molecular weight was added to 600g of the copper powder for surface treatment, and stirred at 350rpm for 60 minutes at room temperature to adsorb malonic acid on the surface of the particles, and then washed and dried to produce copper powder.
[0071] (Comparative Example 2)
[0072] Obtain commercially available copper powder.
[0073] (evaluate)
[0074] The copper powders of the above-mentioned inventive examples 1 to 5 and comparative examples 1 and 2 were subjected to the above-mentioned measurement methods, etc., to confirm the BET specific surface area, particle size, carbon content, oxygen content, low temperature sintering property, and peak areas A1, A3, and A2. The results are shown in Table 1. It should be noted that, for reference, the C1s spectrum obtained by XPS of inventive example 5 is shown in Figure 1 .
[0075] [Table 1]
[0076]
[0077] As shown in Table 1, the C / SSA of Inventive Examples 1 to 5 is less than 0.07, and the peak area ratio (A2 / A1) is greater than 0.5. Therefore, the results of the 5% shrinkage temperature obtained by TMA show that the low temperature sintering property is excellent. Among them, the 5% shrinkage temperature obtained by TMA of Inventive Examples 2 to 5 with a peak area ratio (A3 / A1) greater than 0.3 is less than 280°C.
[0078] On the other hand, since C / SSA of Comparative Example 1 was greater than 0.07, the 5% shrinkage temperature obtained by TMA was high. Since the peak area ratio (A2 / A1) of Comparative Example 2 was less than 0.5, the 5% shrinkage temperature obtained by TMA was high.
[0079] Therefore, it can be said that the copper powders of Invention Examples 1 to 5 are excellent in low-temperature sinterability.
Claims
1. A copper powder, wherein The ratio of carbon content C to BET specific surface area C / SSA is less than 0.07, wherein the unit of carbon content C is mass %, and the unit of BET specific surface area is m 2 / g, In the C1s spectrum obtained by X-ray photoelectron spectroscopy, the peak area ratio A2 / A1 of the peak area A2 having a peak top in the range of 288 eV to 289.2 eV to the peak area A1 having a peak top in the range of 284 eV to 285 eV is 0.5 or more.
2. The copper powder according to claim 1, wherein In the C1s spectrum obtained by X-ray photoelectron spectroscopy, the peak area ratio A3 / A1 of the peak area A3 having a peak top in the range of 286 eV to 288 eV to the peak area A1 having a peak top in the range of 284 eV to 285 eV is 0.3 or more.
3. The copper powder according to claim 1 or 2, wherein The peak area ratio A2 / A1 is 1.0 or less.
4. The copper powder according to claim 1 or 2, wherein The BET specific surface area of the copper powder is 0.5 m 2 / g~10.0m 2 / g.
5. The copper powder according to claim 1 or 2, wherein The average particle size calculated from the BET specific surface area is 0.05 μm to 2.00 μm.
6. The copper powder according to claim 1 or 2, wherein The ratio of oxygen content O to BET specific surface area O / SSA is greater than 0.15, the unit of the oxygen content O is mass %, and the unit of the BET specific surface area is m 2 / g.
Citation Information
Patent Citations
Copper powder, copper paste, method for manufacturing conductive coating film, and conductive coating film
WO2012157704A1